Gendered Conversational Rituals on the Internet: An Effective Voice Is Based on More than Simply What One Is Saying - Cushing, Pamela J. (Anthropologica, 2022)
The author uses ethnographic evidence to highlight the dearth of female voices and actors in the emerging information technology (IT) field. She uses a model of archetypal linguistic patterns to illustrate how male rituals prevail. She outlines the historical power relations, and medium-specific traits that help to explain why the male linguistic bias persists even as females enter the field. The Conversational Rituals Model employed here is grounded in established gender theory, and in particular in Tannen's sociolinguistic research (1990, 1994). The communications of both Users and Innovators are analyzed in terms of Purpose, Environment, Style and Content. The author demonstrates that when the male linguistic style is privileged to the exclusion of others, it is problematic because (1) the reduction in diversity diminishes the overall quality of the medium and (2) it creates systemic barriers to effective participation by sub-dominant groups by indirectly forcing them to adapt to the dominant male conversational norms in order to communicate effectively. By framing IT communications with theories of the contingency of language (Davidson 1984; Rorty 1989), and the cultural-biases inherent in public spaces (Fraser 1994), the author argues that intervention is justified and vital. Potential solutions are discussed